Pesticidal Evaluation of Entomopathogenic Fungi and Selected Medicinal Plants against Cabbage Aphid (Brevicoryne brassicae L.) - Gebreegziabher Gebreyohans; Nafyad Ibrahim Batu; Jagathala Mahalingam Sasikumar (Advances in Agriculture)
Pesticidal agents such as entomopathogenic fungi and medicinal plant extracts can be used as a component of integrated pest management. Biocontrol agents such as fungal isolates can be used as a component of integrated pest management. An evaluation of plant extracts from Azadirachta indica and Justicia schimperiana and two strains of entomopathogenic fungi were carried out on Ethiopian rape (Brassica carinata) against two stages (adult and nymph) of cabbage insect pests (aphids) in the laboratory and greenhouse condition. The efficacies of different treatments were examined, and results were recorded for plant extracts and entomopathogenic fungi on cabbage aphids. A significant difference was observed in the mortality of aphid insect pests recorded at different intervals of days. The adult aphid was reduced gradually from 8.65/plant to 2.77/plant after six days of spraying with A. indica indicating the highest efficacy. Moreover, the adult aphids after spraying of entomopathogenic fungi (BEI1) reduced from 11.2/plant to 6.5/plant after six days of spraying at 1 × 108 conidia/mL, showing the highest efficacy. The present results suggest the possibility of using a combination of entomopathogenic fungi and plant extracts to manage Brevicoryne brassicae (aphids). It revealed that a given combination displayed considerable efficacy to reduce B. brassicae (aphids) infestation. From the result, the adult aphids sprayed with A. indica + BEI1 reduced from 7.01/plant to 1.74/plant after six days of spraying with the highest efficacy. Generally, maximum percent of mortality was identified in plant extract treatment next to coapplication against adult aphids on sixth day of application. Similarly, conidial suspension of entomopathogenic fungi was found to have high activities for adult aphids. Therefore, based on the present result, products of fungal isolates and plant extracts should be used for further tests against other insect pests.